Twee versoenbare konstrukte in resente historiese Jesus-navorsing, Deel I: John Dominic Crossan 1 - Wyk, D. J. C. van (Hervormde teologiese studies, 2000)
Two compatible constructs in current historical Jesus research, Part I: John Dominic Crossan. Current historical Jesus research produces a variety of profiles of Jesus. In a series of articles two compatible constracts of Jesus (those of John Dominic Crossan and Andries van Aarde) will first be discussed and, second, two ireconcilible constructs (those of Robert F Funk and Walter Schmithals). The profiles of Jesus are depicted from the perspective of the researcher's view on the continuity and discontinuity between Jesus and early Christianity and the relevance of historical Jesus research for church and theology. This article focuses on John Dominic Crossan's view on Jesus the peasant.